2013
DOI: 10.1007/s10067-013-2387-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of tuberculosis incidence in ankylosing spondylitis and rheumatoid arthritis during tumor necrosis factor inhibitor treatment in an intermediate burden area

Abstract: Clinical characteristics of antitumor necrosis factor (TNF) agents-related tuberculosis (TB) in ankylosing spondylitis (AS) are not well described. The aim was to compare the incidences and the characteristics of TB in AS and rheumatoid arthritis (RA) during TNF inhibitor treatment. AS (n = 1,322) and RA (n = 3,154) patients who received medical care between January 2001 and August 2011 were enrolled. The incidence of TB in patients treated, or not, with TNF inhibitors and the clinical features associated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 28 publications
3
29
0
2
Order By: Relevance
“…There were no cavitary lesions or consolidation noted in half of the TB patients. Extrapulmonary manifestation was higher in patients receiving anti-TNF-a therapy than in the general population, which has also been shown in previous studies [6,9,10]. These findings may be explained by systemic spreading of mycobacteria due to inhibition of TNF-a by anti-TNF-a therapy in TB patients [28,29].…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…There were no cavitary lesions or consolidation noted in half of the TB patients. Extrapulmonary manifestation was higher in patients receiving anti-TNF-a therapy than in the general population, which has also been shown in previous studies [6,9,10]. These findings may be explained by systemic spreading of mycobacteria due to inhibition of TNF-a by anti-TNF-a therapy in TB patients [28,29].…”
Section: Discussionsupporting
confidence: 83%
“…Clinical data on TB in patients treated with TNF-a antagonists have been extensively reported in several studies [4,6,7,9,10]. In addition, as clinicians are concerned about the development of TB in patients treated with TNF-a inhibitors, there is a focus on screening and treating latent TB infection (LTBI) before administering TNF-a inhibitors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also agents used for the treatment of rheumatoid arthritis may further increase the risk of TB [34,35,36]. Recently, Kim et al [37] reported that the TB incidence in ankylosing spondylitis and rheumatoid arthritis patients receiving aTNF-α-T is similar, and EP-TB was prevalent in both conditions. On the other hand, a higher risk of TB was observed in patients diagnosed with Behçet's disease in our study (p = 0.003), consistent with some previous reports suggesting an association between an elevated TB risk and Behçet's disease [38,39].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, compared with subjects naive to anti-TNF therapy, the incidence of tuberculosis is multiplied by a factor of four in RA and in AS, and this irrespective of the anti-TNF drug. Age > 60 years in RA (OR 15.9, 95% CI: 1.8-147.6), and BMI < 22 kg/m 2 in AS (OR 13, 95% CI: 1.51-111.92) were significant risk factors for this complication [39]. There appear to be large differences between the different anti-TNF drugs.…”
Section: An Eye On Safetymentioning
confidence: 95%